Monetary and exchange rate policy in 1997 (1997)
This article presents a brief review of the monetary and exchange rate program of the Banco de la República for 1997; describes its goals and the forms in which the instruments available to it were used; and looks at the most relevant factors in the evolution of the control variables and intermediate goals. The conclusion of this review is that the monetary and exchange rate policy announced by the Board of Directors af the Banco de la República since 1996 has been fully carried out, and that all indications are that at the end of the year the predicted inflation goal will be met.